2012
DOI: 10.2174/1876396001205010045
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition in Chronocardiology: We are Indebted Professor Franz Halberg

Abstract: Abstract:Franz Halberg had very many experiences in India. The word circadian and chronobiology, chronocardiology and chronoastrobiology were coined by him. He also discovered that in studies of single daily meals, eating breakfast was associated with weight loss compared to dinner, despite similar energy intake. The role of time-adjusted drug intake, especially in the early morning, was also known to ancient Indian physicians. In Ayurveda, drinking of large amounts of water in the early morning is advised, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 124 publications
(269 reference statements)
1
7
0
Order By: Relevance
“…Omega-3 fatty acid is also known to control mental load and behavior [24]. There is consistent evidence that fruit and vegetable rich diet can decrease blood pressures and modulate CVDs [28][29][30][31][32]. Singh et al reported for the first time by ambulatory blood pressure monitoring, about half weekly pattern of blood pressure and heart rate in men and women of India as well as circadian decrease in antioxidant vitamins and increased oxidative stress in the second quarter of 24 hours [33,34].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Omega-3 fatty acid is also known to control mental load and behavior [24]. There is consistent evidence that fruit and vegetable rich diet can decrease blood pressures and modulate CVDs [28][29][30][31][32]. Singh et al reported for the first time by ambulatory blood pressure monitoring, about half weekly pattern of blood pressure and heart rate in men and women of India as well as circadian decrease in antioxidant vitamins and increased oxidative stress in the second quarter of 24 hours [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…It also recognizes that over one-third of 72 million Americans said to be treated for hypertension can have a great conventionally unrecognized risk increase that can often be removed by adjusting the timing of antihypertensive drugs. Chronobiologically, computerimplemented self-surveillance of blood pressure and heart rate by 7-day/24-h monitoring detects conditions to which conventional treatment is now blind [4][5][6][7][8][9][26][27][28]. In the present case, we describe that a Western diet and lifestyle can predispose VVDs which may be reversed by changing to a wild type diet and lifestyle.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…This observation is quite important for developing societies who were under-nutrition in 1950s after World War II, but eating a larger breakfast comprising of 1000 calories, may result into circadian increase in cardiovascular events in between 6.00-1200 hours among societies with overnutrition such as in affluent societies now [47]. It would be pertinent to select functional foods for the breakfast comprising of about 500 K Cal to have the beneficial effects of functional nutrients as well as of increased energy metabolism in the morning as advised by Halberg et al, causing no increase in body weight Fig.…”
Section: Nutrition In Transition and Diet Linked Chronic Diseasesmentioning
confidence: 99%